Enhancing Iodine Capture of Porous Organic Cages through N-Heteroatom Engineering - Zou, Ding (Langmuir : the ACS journal of surfaces and colloids, 2024)
Iodine radioisotopes, produced or released during nuclear-related activities, severely affect human health and the environment. The efficient removal of radioiodine from both aqueous and vapor phases is crucial for the sustainable development of nuclear energy. In this study, we propose an "N-heteroatom engineering" strategy to design three porous organic cages with N-containing functional groups for efficient iodine capture. Among the molecular cages investigated, FT-Cage incorporating tertiary amine groups and RT-Cage with secondary amine groups show higher adsorption capacity and much faster iodine release compared to IT-Cage with imine groups. Detailed investigations demonstrate the superiority of amine groups, along with the influence of crystal structures and porosity, for iodine capture. These findings provide valuable insights for the design of porous organic cages with enhanced capabilities for capturing iodine